MENINGKATKAN PENGETAHUAN MASYARAKAT TENTANG KERACUNAN KEHAMILAN - Vivi Setiawaty (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2006)
Prenatal Mortality Rates and Maternal Mortality Rates in Indonesia still high because of many factors and pre-eclamsia/eclamsi is one of that. However the uncomplete knowledge of the community about pre-eclamsia have lead to the indication malpractice done by doctors or midwifes. Pre-eclamsia actually is a common complication of pregnancy. It is mild in many cases but in some cases it becomes severe, and can cause serious complications. The condition goes when the baby is born . Medication may be advised to help prevent complications